2016
DOI: 10.1016/j.apm.2015.09.043
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seismic intensity parameters on structural damage of RC buildings using principal components analysis

Abstract: Please cite this article as: Ali Massumi , Fatemeh Gholami , The influence of seismic intensity parameters on structural damage of RC buildings using principal components analysis, Applied Mathematical Modelling (2015),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…A general evaluation of relationships between various engineering demand parameters (EDPs) and cumulative-, spectrum-, and amplitude-based GMIMs including AI and CAV is summarized in Cosenza and Manfredi (2000), Riddell (2007), Kadaş and Yakut (2013), Ye et al (2013), Mollaioli et al (2013), Ebrahimian et al (2015), and Kostinakis et al (2018). In addition, several investigators have found that AI, CAV, or both sometimes in combination with other GMIMs are optimally correlated with EDPs proposed for buildings and bridges (e.g., Padget et al 2008, Fontara et al 2011, Katona 2012, Elenas 2013, Mollaioli et al 2013, Katona and Tóth 2013a, 2013b, Ebrahimian et al 2015, Hancilar and Çakti 2015, Perrault and Guéguen 2015, Tarbali and Bradley 2015, Massumi and Gholami 2016, Kiani and Pezeshk 2017, Muin and Mosalam 2017, Fiore et al 2018, Jahangiri et al 2018, Kiani et al 2018, Liang et al 2018, Mashayekhi et al 2018, Wang et al 2018). Other investigators have developed relationships correlating these GMIMs with amplitude- and spectrum-based GMIMs (e.g., Wang and Du 2012, Bradley 2012, Du and Wang 2013a, Liu et al 2016, Xu et al 2016) and ground motion duration measures (Bradley 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A general evaluation of relationships between various engineering demand parameters (EDPs) and cumulative-, spectrum-, and amplitude-based GMIMs including AI and CAV is summarized in Cosenza and Manfredi (2000), Riddell (2007), Kadaş and Yakut (2013), Ye et al (2013), Mollaioli et al (2013), Ebrahimian et al (2015), and Kostinakis et al (2018). In addition, several investigators have found that AI, CAV, or both sometimes in combination with other GMIMs are optimally correlated with EDPs proposed for buildings and bridges (e.g., Padget et al 2008, Fontara et al 2011, Katona 2012, Elenas 2013, Mollaioli et al 2013, Katona and Tóth 2013a, 2013b, Ebrahimian et al 2015, Hancilar and Çakti 2015, Perrault and Guéguen 2015, Tarbali and Bradley 2015, Massumi and Gholami 2016, Kiani and Pezeshk 2017, Muin and Mosalam 2017, Fiore et al 2018, Jahangiri et al 2018, Kiani et al 2018, Liang et al 2018, Mashayekhi et al 2018, Wang et al 2018). Other investigators have developed relationships correlating these GMIMs with amplitude- and spectrum-based GMIMs (e.g., Wang and Du 2012, Bradley 2012, Du and Wang 2013a, Liu et al 2016, Xu et al 2016) and ground motion duration measures (Bradley 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the corresponding accelerogram signalẍ g (t). In the next section the Arias Intensity (i A ) is used to quantify the earthquake acceleration power [3]. The Arias Intensity is defined as:…”
Section: Algorithm 1 Stochastic Accelerogram Generationmentioning
confidence: 99%
“…In Refs. [8,9] principal component analysis (PCA) is used to select feature. Other feature selection methods for bridge structural diagnosis include local linear embedding (LLE) [10,11], independent component analysis (ICA) [12,13], isometric mapping algorithm [14], and .…”
Section: Introductionmentioning
confidence: 99%